Innovation For Sustainability : African and European Perspectives - Baskaran, Angathevar; Muchie, Mammo (UPCC book collections on Project Muse., 2012)
The innovation system theory has to deal with climate change as it generates the intellectual tools to promote development. A unified innovation system theory that integrates the eradication of threats to nature with the promotion of development is critically important to advance an original pedigree and trajectory of epistemology. Africa must learn and appreciate the costs to itself from the way Europe industrialised. It can neither follow nor imitate the European pattern of industrialisation. It has to include in its own development agenda both the meeting of social needs and choosing a path of development that would not bring ecological harm in the process. The African innovation system has to evolve in a nature protecting, rather than hurting, system; in addition, social needs must be met rather than exacerbating the social inequalities path of development.